HUBUNGAN SIKAP DENGAN KEPATUHAN PERAWAT DALAM PENGISIAN FALL RISK ASSESSMENT DI RS KALIMANTAN SELATAN: The Relationship Between Attitudes And Nurse Compliance In Filling Fall Risk Assessment At The South Kalimantan Hospital - Astuti, Noormailida; Saputra, Adisurya; Setyawati, Febri (Jurusan Keperawatan, 2024)
Patient safety is part of hospital services by providing a sense of security and comfort to patients when receiving health services. One of the components of patient safety in the prevention of fall risk that nurses can do is to fill out a fall risk assessment. Objective: To determine the relationship between attitudes and nurse compliance in filling out the fall risk assessment at the South Kalimantan Hospital. Methods: The research uses a type of correlational descriptive research with a cross sectional design. The research population was all nurses in the Class I/II Internal Medicine Room, Class III Internal Medicine Room and Class II/III Surgery Room at South Kalimantan Hospital, totaling 70 people. Samples were taken by sampling technique using the total sampling method. Research data obtained from questionnaires, the data were analyzed through Chi-Square statistical test. Results: From the univariate analysis showed that nurse’s attitudes was mostly in the positive category as much as 88.6%, while nurse’s compliance in filling the fall risk assessment was mostly in the obedient category as much as 90%. From the bivariate analysis showed that there was a significant relationship between attitudes and nurse compliance in filling fall risk assessment with p value = 0,001. Conclusions: It is expected that the hospital can improve the control and supervision of the head of the room on the nurse, so that the filling of the fall risk assessment carried out by the nurse can be better. Keselamatan pasien merupakan bagian dari pelayanan rumah sakit dengan memberikan rasa aman dan nyaman pada pasien ketika menerima jasa layanan kesehatan. Salah satu komponen keselamatan pasien dalam pencegahan risiko jatuh yang dapat dilakukan perawat adalah dengan melakukan pengisian fall risk assessment. Tujuan: mengetahui hubungan sikap dengan kepatuhan perawat dalam pengisian fall risk assessment di RS Kalimantan Selatan. Metode: penelitian ini menggunakan jenis penelitian deskriptif korelasional dengan rancangan cross sectional. Populasi penelitian adalah seluruh perawat di Ruang Penyakit Dalam Kelas I/II, Ruang Penyakit Dalam Kelas III dan Ruang Bedah Kelas II/III RS Kalimantan Selatan sebanyak 70 orang. Sampel diambil dengan teknik pengambilan sampel menggunakan metode total sampling. Data penelitian diperoleh dari lembar kuesioner, data dianalisa melalui uji statistik Chi-Square. Hasil: Hasil penelitian dari analisis univariat menunjukkan sikap perawat sebagian besar pada kategori positif sebanyak 88.6%, sedangkan kepatuhan perawat dalam pengisian fall risk assessment sebagian besar pada kategori patuh sebanyak 90%. Dari analisis bivariate menunjukkan bahwa ada hubungan sikap dengan kepatuhan perawat dalam pengisian fall risk assessment dengan nilai p = 0,001. Kesimpulan: diharapkan pihak rumah sakit dapat meningkatkan kontrol serta pengawasan kepala ruangan pada perawat, sehingga pengisian fall risk assessment yang dilakukan oleh perawat dapat lebih baik.